Comparative Analysis of the Effect of Organoclay, Boron Nitride, and Fluoropolymer on the Rheology and Instabilities in the Extrusion of High Density Polyethylene - A. A. Adesina; M. S. Nasser; I. A. Hussein (International Journal of Polymer Science)
The effect of different processing additives on the extrusion instabilities of high density polyethylene (HDPE) was investigated. The concentration of each processing additive was fixed at 0.05 wt%. Organoclay, boron nitride, and fluoropolymer reduced transient shear and extensional viscosities of HDPE melt. Drop in extrusion pressure occurred during the extrusion experiment. The initial loss of glossiness in HDPE was restored with the addition of these additives. However, the fluoropolymer did not succeed in eliminating the stick-slip fracture. Despite the inclusion of the processing additives, gross-melt fracture in HDPE reappeared at apparent shear rate of 141 s−1. Both moment and distortion factor methods of analyses were employed and their findings support the observed visual trends of the extrudate surface. The quantifying tools indicated that combined organoclay and fluoropolymer reduced the pressure fluctuations and its performance surpassed that of the individual additives.